Clinical research of drug-coated balloon after rotational atherectomy for severe coronary artery calcification - Haozhe Dong; Yingguang Shan; Shenzhen Gong; Ran Li; Yiming Li; Xupeng Lu; Guoju Sun (BMC Cardiovascular Disorders, 2023)
Abstract Background Current research results show that drug-coated balloons (DCB) have unique advantages in the treatment of in-stent restenosis, small vessel disease, bifurcation lesions, and de novo lesions, but the data regarding rotational atherectomy (RA) followed by DCB treatment in calcified lesions, especially severe coronary artery calcification (CAC), are limited. Methods A retrospective study was conducted on 318 individuals with severe CAC who underwent RA-assisted PCI at the First Affiliated Hospital of Zhengzhou University from May 2018 to July 2021. Among them, 57 patients (RA/DCB group) were treated with DCB, and 261 patients (RA/DES group) were treated with drug-eluting stents (DES). The two groups' clinical baseline data, lesion characteristics, intraoperative complications, in-hospital adverse events, and major adverse cardiovascular and cerebrovascular events (MACCE) were compared throughout the follow-up period. Results The baseline clinical data, intraoperative complications, and in-hospital adverse events were not significantly different between the two groups. The anatomical categories in the RA/DES group were more complex and included left main coronary disease, bifurcation disease, and multivessel disease. Although target lesion revascularization (13.79% vs. 7.02%) and MACCE (18.77% vs. 12.28%) occurred more frequently in the RA/DES group than in the RA/DCB group, there was no statistically significant difference (p > 0.05). Multivariate Cox regression analysis showed that bifurcation lesions (HR 2.284, 95% CI 1.063–4.908, p = 0.034), total length of DCB/DES (HR 1.023, 95% CI 1.005–1.047, p = 0.014) and SYNTAX score (HR 1.047, 95% CI 1.013–1.082, p = 0.006) were independent risk factors for MACCE during the follow-up period. Conclusion Drug-coated balloon treatment after rotational atherectomy appears safe and effective in selected severe coronary artery calcification.